L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Nursing students’ well-being: A comparison of two canadian nursing programs in different linguistic contexts - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Vigier, Darcelle; Waddell, Candice; Graham, Jan Marie (Linguistic Minorities and Society, 2022)
Nursing programs are highly competitive and stressful environments; nursing educators are looking for ways to mitigate the negative consequences of demanding training programs. This article explores and compares the mental health status and sociodemographic and personal characteristics that influence the psychological distress of nursing and non-nursing students learning in either official language of Canada. An online and paper survey was administered during class time to 990 students, 186 of whom were in an undergraduate nursing program in one of two postsecondary institutions in Manitoba, Canada. Findings demonstrate that students in nursing programs are more likely to report poor mental health than students in other undergraduate programs and that nursing students in the French-language institution report poorer mental health outcomes as compared to nursing students in the English-language institution. Life satisfaction and high self-esteem are positively associated with well-being, whereas age, gender, and learning in a second language are risk factors contributing to anxiety. Keywords: mental health, risk behaviour, nursing students, linguistic minority, risk factors

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)